Research on controlling of experiment model to evaluate of kinetic energy recovery system based on driving cycles - Duong, Tuan Tung; Do, Van Dung; Nguyen, Truong Thinh (Journal of Technical Education Science, 2018)
The inertia of the automobile during braking and deceleration is enormous. In a conventional vehicle, this energy has not been recovered but is converted into heat at the braking mechanism. In this study, an experimential model will be built to calculate the energy recovered during braking or deceleration in a vehicle with the conventional powertrain. This study model includes: A motor-driven an axle; a magnetic brake and torque measuring device at the drive wheel to control the traction and braking force in the vehicle; a double planetary gear set to change the ratio paralleled to the propeller shaft to rotate the flywheel whenever braking or deceleration is performed; a generator is coaxial with the flywheel to convert the mechanical energy into electricity rechargeable for battery. Moreover, the PID controller is built to control the energy kinetic energy recovery system during braking or deceleration according to the driving cycles such as FTP75, NEDC, EUDC and ECE R15. Experimental results show that the energy recovery efficiency can achieve about 27.87% to 38.25% depending on the driving cycle.